(untitled) (World Economics and Finance Bulletin, 2025)
The article discusses the importance of Gap Analysis and Cost-at-Risk (CaR) models in improving interest rate risk and asset-liability management (ALM) processes in the activities of commercial banks in Uzbekistan. First, based on the recommendations of the Basel Committee, the concept of interest rate risk, its impact on bank profitability and capital, and the theoretical foundations of the repricing gap (gap) model are analyzed. Then, the CaR model is considered as an integrated risk indicator that assesses the distribution of interest expenses in a similar way to the Value-at-Risk (VaR) approach.